Empirically Supported Psychotherapies Comment on Westen, Novotny, and Thompson-Brenner (2004). [article]. - Crits-Christoph, Paul
D. Westen, C. M. Novotny and H. Thompson-Brenner (2004) suggested that efforts to identify emperically supported treatments are misguided because they are based on assumptions that are not appropriate for some types of treatment and patient. The authors of this comment argue that Westen and collegues are simply incorrect when they insert that empirically supported treatments require that psychopathology must be highly malleable, that treatments must be brief, or that the samples studied are unpresentative of the kinds of patients typically encountered in clinical practice--comorbidityis common in many clinical trials. Randomized controlled trials remain the most powerful way to test notions of causal agency.-- (from the author)
Keywords: Psychology-Periodicals.; Empirically supported psychotherapies; Randomized clinical trials; Comorbidity